Milk-clotting proteases from Pleurotus albidus: an innovative alternative for the production of Minas frescal cheese - Martim, Salomão Rocha (2021)
Pleurotus albidus, a naturally growing species in the Amazon region, has been considered a promising source of milk-clotting proteases. The production of such enzymes using lignocellulosic residues is a sustainable alternative to replace mammalian rennet. The application of P. albidus milk-clotting proteases in cheese making has not yet been reported in the scientific literature. The aim of this study was to characterize the milk-clotting proteases of P. albidus and use these enzymes in the production of Minas frescal cheese. For the production of coagulating proteases, the mushroom was grown in açaí seeds supplemented with rice bran (10%, w/w). The parameters affecting the production of coagulant, such as inoculum size, fermentation time, initial pH of cultivation medium and age of the inoculum were evaluated. The coagulant extract obtained under optimal production conditions was evaluated for optimal pH and temperature, pH and temperature stability, effect of ions and inhibitors. Significant production of coagulating proteases was obtained under the following conditions: inoculum size (2.5%), fermentation time (10 days), initial pH of the cultivation medium (6), and inoculum age (10 days). The coagulant exhibited significant catalytic activity in pH 5.0 at 55°C, with stability at 45°C and was completely inhibited by iodoacetic acid. The milk-clotting proteases of P. albidus were efficient for making Minas frescal cheese that presented 55.0% of moisture, 20.0% of lipids and 17.20% of protein. Pleurotus albidus is a potential source of milk-clotting proteases that can be applied in dairy industry for production of fresh Minas frescal cheese.